1999
DOI: 10.1038/sj.onc.1202830
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A-Iα subunit-directed antisense inhibition of ovarian cancer cell growth: crosstalk with tyrosine kinase signaling pathway

Abstract: Expression of the RIa subunit of cAMP-dependent protein kinase type I is increased in human cancers in which an autocrine pathway for epidermal growth factorrelated growth factors is activated. We have investigated the e ect of sequence-speci®c inhibition of RIa gene expression on ovarian cancer cell growth. We report that RIa antisense treatment results in a reduction in RIa expression and protein kinase A type I, and inhibition of cell growth. The growth inhibition was accompanied by changes in cell morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…2A also expressed regulatory subunits (data not shown), indicating the existence of functional PKA complexes in these cells. This is in agreement with previous reports showing a frequent activation of PKA in ovarian cancer (30,31). Claudin-3 expression was absent in non-malignant HOSE-B cells but found in most of the ovarian cancer lines.…”
Section: Expression Of Pka Catalytic and Claudin-3 Proteins In Ovariasupporting
confidence: 83%
See 1 more Smart Citation
“…2A also expressed regulatory subunits (data not shown), indicating the existence of functional PKA complexes in these cells. This is in agreement with previous reports showing a frequent activation of PKA in ovarian cancer (30,31). Claudin-3 expression was absent in non-malignant HOSE-B cells but found in most of the ovarian cancer lines.…”
Section: Expression Of Pka Catalytic and Claudin-3 Proteins In Ovariasupporting
confidence: 83%
“…PKA activation has been suggested to have a role in TJ disruption (32), and claudin-3 phosphorylation may represent one of the targets to achieve this physiological outcome. Interestingly, PKA is often activated in ovarian cancer (30,31). In addition, our unpublished work 2 suggests that claudin overexpression in ovarian cancer cells may contribute to an increase in invasion and survival of these cells, mediated at least in part through the breakdown of TJs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of (54, 55) PKC inhibits apoptosis in several cell types (51,56). Moreover, PKC is up-regulated in a wide range of cancers (51,57). However, also pro-apoptotic activities of PKC have been reported, and it is assumed that the different functions of this kinase in apoptosis might be exerted by distinct isoenzymes (51).…”
Section: Discussionmentioning
confidence: 99%
“…PKA is the classical intracellular cAMP receptor and has been shown to be upregulated in a number of cancers, including ovarian cancer (Alper et al, 1999;Amsterdam et al, 1999;McDaid et al, 1999). Studies using a cAMP response element (CRE)-decoy in ovarian cancer cells have shown that the subset of genes activated by CRE are critical to controlling apoptosis, growth, and invasion (Alper et al, 1999).…”
Section: Discussionmentioning
confidence: 99%